2016
DOI: 10.1155/2016/5419737
|View full text |Cite
|
Sign up to set email alerts
|

Myxoid Chondrosarcoma of Maxilla in a Pediatric Patient: A Rare Case Report

Abstract: Myxoid variant of chondrosarcoma is an uncommon potentially lethal malignant tumor which is even rare in pediatric age group. In the present paper, we report one such case of intermediate grade myxoid chondrosarcoma of left side of maxilla in a 12-year-old girl. The present case had a firm, painless, and lobulated growth in premolar-molar region which was associated with bicortical expansion. Maxillofacial imaging showed ill-defined radiolucency with displaced maxillary molars. Osteolytic changes were evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Clinical features of chondrosarcomas like paresthesia and dysesthesia, are used to differentiate a malignant neoplasm from osteomyelitis. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features of chondrosarcomas like paresthesia and dysesthesia, are used to differentiate a malignant neoplasm from osteomyelitis. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcoma is a rare bone and soft tissue tumor, 13 but it is the most common primary malignant chest wall tumor, with better long-term survival compared to other chest wall sarcomas. 4 , 5 The metastatic potential of these tumors is important. Some authors have reported that chest wall chondrosarcoma has poor outcomes related to distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that chest wall chondrosarcoma has poor outcomes related to distant metastasis. 5 The prognostic factors of this tumor include age at diagnosis, tumor stage, tumor grade, chondrosarcoma subtype, surgery, and radiotherapy. 2 Some subtypes of chondrosarcoma respond differently to the various adjuvant treatments (chemotherapy is efficient in mesenchymal chondrosarcoma), and low-grade chondrosarcomas rarely metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CT scan is more sensitive than MRI for detection of calcifications. CT scan may demonstrate an ill-defined cloud-like matrix with calcified whorls and arcs [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%